KOMBINASI EFEKTIF EKSTENDER DAN KRIOPROTEKTAN PADA KRIOPRESERVASI SPERMA IKAN NILEM (Osteochilus hasseltii Valenciennes, 1842) - A. Sunarma; D. W. B. Hastuti; D. M. Saleh; Y. Sistina (Universitas Gadjah Mada, 2008)
Cryopreservation technology of fish sperm has been developed to prolong gamete viability. Combination of two extenders (ringer or glucose) and two cryoprotectans (DMSO or methanol) on three concentrations have studied to sperm cryopreservation of nilem. Nilem fish brooder induced by GnRHa and domperidone combination. Sperm was diluted in extender at the ratio of 1:9 then cryoprotectant was added at 5%, 10% or 15% (v/v) concentrations. Samples were stored in 0,5 mL straws, equilibrated at temperature 4 – 5 oC for 20 minutes, vaporized at 3 cm above surface liquid nitrogen for 3 minutes and then plunged into liquid nitrogen, where they were stored for 1 weeks. Sperm was thawed at temperature 39 – 40 oC for 10 – 15 sec. and was used to fertilize 100 – 200 eggs per straw. The highest percentage of post-thawed sperm was combination ringer and DMSO 10% (87.50 ± 5.00%) and the lowest was combination ringer and methanol 5% (23.75 ± 4.79%). The highest hatching rate fertilized by post-thawed sperm was combination ringer and DMSO 15% (54.98 ± 28.61%) and the lowest was combination glucose and DMSO 15% (6.54 ± 3.32%). The study proven combination of ringer extender and DMSO cryoprotectant effective for cryopreservation of Indonesian silver sharkminnow fish sperm. Therefore, fish sperm cryopreservation with nilem as a representative model could be developed to extend on other Cyprinidae.